Clinical symptoms and results of autonomic function testing overlap in spontaneous intracranial hypotension and postural tachycardia syndrome - Nina Graf; Ana Mafalda Fernandes Santos; Christian T Ulrich; Christian Fung; Andreas Raabe; Jürgen Beck; Werner J Z'Graggen (SAGE Publishing, 2018)
Background and purpose: Orthostatic headache is a hallmark of patients with spontaneous intracranial hypotension (SIH) but may also occur in patients with postural tachycardia syndrome (POTS). Our aim was to compare the clinical symptoms and findings of autonomic function testing in patients with SIH and POTS. Methods: This was a retrospective analysis of the clinical symptoms and findings of autonomic function testing, including sympathetic vasoconstrictor and parasympathetic cardiac function as well as head-up tilt in patients with SIH and POTS. Results: Nine patients with confirmed SIH and 48 with POTS (neuropathic N = 35, hyperadrenergic N = 5, deconditioned N = 8) were included. SIH patients experienced on average a shorter disease duration than patients with POTS. Orthostatic headache was present in all patients with SIH and 27% of patients with POTS. There was a broad overlap of other clinical symptoms of orthostatic intolerance. Screening autonomic function testing revealed normal sympathetic and parasympathetic function in all patients. All patients with SIH showed an excessive clinically symptomatic heart rate increase during standing, fulfilling the diagnostic criteria for POTS. Conclusion: Clinical symptoms and results of autonomic function testing overlap in SIH and POTS. Hence, patients with prominent orthostatic headache fulfilling the diagnostic criteria for POTS should also be evaluated for further testing of a spinal cerebrospinal fluid leak, in the absence of a history of lumbar puncture.